Efektivitas Kerja Karyawan Bank Nagari Unit Layanan Syariah Tapan - Sandri Saputra; Mursal Mursal (Journal Islamic Economic and Bussines Studies, 2022)
Good employee effectiveness is certainly obtained from the work of every employee who does his job correctly and on time. Thus, work as something that will appear, where the individual in achieving the goals of the organization. Good work is one of the goals of an organization or an institution in achieving high effectiveness. Achieving good work cannot be separated from the quality of good human resources. So, in this study the researcher wanted to see the work effectiveness of employees at Bank Nagari Syariah Service Unit Tapan which only has 1 permanent employee and is seconded by permanent employees from the general service unit. The type of research used is descriptive research, types of research data, primary data, and secondary data. data sources, research subjects and objects, data collection techniques and data analysis techniques.